Analysis of Character Building through Habituation to Happiness based on Al-Misbah Interpretation - Mundiatul Mila; Abdul Ghofur (KURAS Institute, 2025)
This study examines how selected Qur’anic verses, Surah Āl ‘Imrān 191, Surah ar-Ra‘d 11, and Surah al-Isrā’ 78–79, conceptualize moral flourishing and psychological well-being, a topic that remains underexplored in contemporary Qur’anic studies and Islamic psychology. While previous research has addressed Qur’anic perspectives on ethics and spirituality, few studies have systematically connected exegetical interpretation with modern theories of eudaimonic well-being and habit formation. Addressing this gap, the study analyzes how M. Quraish Shihab’s Tafsir al-Misbah articulates the relationship between self-concept, moral habituation, and well-being. Using a library research design and a tahlili exegetical approach, this study draws on Tafsir al-Misbah as the primary source and integrates secondary literature on moral psychology, habit theory, and Islamic ethical thought. The analysis shows that Shihab’s interpretation frames well-being as emerging from the alignment of cognitive self-understanding, sustained ethical practice, and reflective awareness. These findings highlight a conceptual convergence between Qur’anic exegesis and contemporary psychological models that emphasize intentionality, consistency, and meaning-making as determinants of eudaimonic well-being. The study contributes to Islamic psychology and Qur’anic studies by proposing a conceptual model that integrates exegetical insights with modern psychological theory, thereby offering a more systematic understanding of how moral habituation functions as a pathway to psychological and spiritual flourishing.